2017
DOI: 10.1186/s12879-016-2167-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of surgical site infection in Ethiopia: prospective cohort

Abstract: BackgroundSurgical site infections are commonest nosocomial infections and responsible for considerable morbidity and mortality as well as increased hospitalizations and treatment cost related to surgical operations. The aim of this study was to determine incidence and predictors of surgical site infections at surgical ward of Hawassa University Referral Hospital, Southern Ethiopia.MethodsWe performed prospective study involving 105 patients that undergone major surgical procedure at Hawassa University Referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
57
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 24 publications
20
57
5
1
Order By: Relevance
“…The association between PROM more than 12hrs and SSI after cesarean section was reported in five [28] In contrast the finding is much higher than studies conducted in Nova Scotia and New Zealand which reported with prevalence SSI 2.7% and 5.2% [29,30]respectively.…”
Section: Factors Associated With Ssi After Cesarean Sectioncontrasting
confidence: 57%
“…The association between PROM more than 12hrs and SSI after cesarean section was reported in five [28] In contrast the finding is much higher than studies conducted in Nova Scotia and New Zealand which reported with prevalence SSI 2.7% and 5.2% [29,30]respectively.…”
Section: Factors Associated With Ssi After Cesarean Sectioncontrasting
confidence: 57%
“…Ethiopia shares the burden of SSIs and the infection rate is reported ranging from 10.9%, in Bahirdar to 19.1% in Hawassa respectively [13,14]. Another study among patients with clinical signs of post-surgical wound infection in Ethiopia, has revealed that the prevalence rate of culture-confirmed SSI was 75% and isolated bacterias have shown multi-drug resistance to the commonly used antibiotics in the hospital in 82.9% of the patients with SSI [15].…”
Section: Introductionmentioning
confidence: 99%
“…,Gao et al (2010),Gil-Londoño et al (2016),Giri et al (2008),Hafez et al (2012),Hao et al (2013),Hernaiz-Leonardo et al (2017),Hey et al (2017),Ibrahim et al (2014),Jyothirmayi et al (2017),Kanafani et al (2006),Khan et al (2010),Khan et al (2011),Ledur et al (2011),Lee et al (2007),Lee et al (2010),Lee et al (2015),Legesse Laloto et al (2017),Leon et al (2011),Li et al (2013),Liu et al (2017),Lyimo et al (2013),Madu et al (2011), El Maerrawi and Carvalho (2015),Malik et al (2009),Martins et al (2008),Marwa et al (2015),Mathur et al (2013),Mawalla et al (2011),Mehrabi Bahar et al (2015),Memon et al (2013),Mundhada and Tenpe (2015),Nagaya et al (2017),Ng et al (2015),Ning et al (2014),Nwankwo and Edino (2014),Oliveira and Carvalho (2004),Pardhan et al (2013), Porras-Hernandez et al (2008,Portillo-Gallo et al (2014),Qi et al (2013),Qin et al (2014),Qiu et al (2011),Rabiu ...…”
mentioning
confidence: 99%